Crystal Structure and Properties of N-Phenyl-N’-(2-nitrobenzoyl)thiourea - Hu, J.H.; Li, Y.; Yan, N.P. (Asian Journal of Chemistry, 2013)
N-phenyl-N’-(2-nitrobenzoyl)thiourea has been synthesized in high yield under PEG-400 as the phase-transfer catalyst. The structure of the synthesized substituted thiourea was determined by single crystal X-ray diffraction. In DMSO solutions, L1 exhibited selective recognition for F–, OAc– and H2PO4–. In addition, the compound is also a considerable plant-growth regulator.